2021
DOI: 10.2196/24208
|View full text |Cite
|
Sign up to set email alerts
|

Impact of App-Delivered Mindfulness Meditation on Functional Connectivity, Mental Health, and Sleep Disturbances Among Physician Assistant Students: Randomized, Wait-list Controlled Pilot Study

Abstract: Background Health care provider and trainee burnout results in substantial national and institutional costs and profound social effects. Identifying effective solutions and interventions to cultivate resilience among health care trainees is critical. Although less is known about the mental health needs of physician assistants (PAs) or PA students, accumulating research indicates that they experience similarly alarming rates of burnout, depression, and emotional exhaustion. Mobile app–delivered mind… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 65 publications
1
11
0
Order By: Relevance
“…15 A randomized controlled trial of 200 PA students using an app to deliver mindfulness meditation showed improved sleep in the group using mindfulness meditation while the control group did not. 16 However, there was no significant improvement in burnout, depression, or anxiety associated with this mindfulness meditation. Despite this, there is evidence that PA students are interested in participating in wellness interventions.…”
Section: Mindfulness Training and Meditationmentioning
confidence: 86%
“…15 A randomized controlled trial of 200 PA students using an app to deliver mindfulness meditation showed improved sleep in the group using mindfulness meditation while the control group did not. 16 However, there was no significant improvement in burnout, depression, or anxiety associated with this mindfulness meditation. Despite this, there is evidence that PA students are interested in participating in wellness interventions.…”
Section: Mindfulness Training and Meditationmentioning
confidence: 86%
“…In one stratified, randomized controlled trial, medical students using the Headspace app reported lower stress and more general well-being (N = 88)14; in another trial, undergraduates using the Calm app improved their self-compassion and mindfulness and reduced stress levels more than controls (N = 88) 11. Findings from a third trial suggested that the 10% Happier app produced sleep improvements and a positive relationship between mindfulness practice and brain connectivity among 14 physician assistant students, albeit no detectable change in anxiety or BO 12. Thus, given the potential for mindfulness phone apps to reduce BO, improve self-compassion, and facilitate other positive outcomes, this study's hypothesis was that practicing self-guided mindfulness via a phone app will improve NICU nurses' professional QOL, specifically by reducing their CF and increasing their CS.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Previous studies have reported equivocal effects of full online MBIs on burnout [2022] and stress [23, 24] in medical personnel. Earlier studies were limited by lack of randomization [2224], lack of a control group [2224] or attention control group [21], underpowered sample size [20,21,23], and had high dropout rates [22, 24]. The outcome effect sizes in many studies have been merely small-to-medium [23, 24].…”
Section: Introductionmentioning
confidence: 99%